Biomass and Carbon Stocks in Different Tree Species of Kaptai National Park, Bangladesh - Rahman, Mohammed Mukhlesur; Al- Amin, M.; Rahman, Syed Hafizur (Indian Forester, 2019)
The aboveground, belowground and total tree biomass along with carbon stocks were estimated in forests of the Kaptai National Park of Bangladesh. These forests are composed of some evergreen and deciduous trees, some of which are natural and others were planted. Seventy seven tracks or reference points, 500 m apart from each other, were selected randomly throughout the park area, and had 4 plots of 10 m radius in each of these tracks. Each plot had an area of 314 m2; so the total sampling area was 9.67 hectares. All the trees in each plot were measured for height and diameter at breast height, which were used to calculate the biomass following an allometric equation. There were 65 tree species in the area; the most dominant trees were Acacia auriculiformis, Dipterocarpus turbinatus, Gmelina arborea, Lagerstroemia speciosa, Swietenia macrophylla and Tectona grandis. Biomass and carbon stocks per tree of these species varied among themselves and with age. The average increment rates in biomass of these species indicated their relative potentials of fixing carbon. However, biomass and carbon stocks of these corresponding tree species were 35.03, 73.86, 23.52, 30.16, 44.49, and 42.67 Mg ha-1. Mean values of aboveground, belowground and total tree biomass were 37.41, 3.86 and 41.27 Mg ha-1 respectively. However, biomass values of some of the tree species differed significantly at P < 0.05 from the others. For example, D. turbinatus had significantly higher biomass than others; G. arborea and L. speciosa were similar but differed from the rest of the tree species. Again, the highest carbon stock per tree was in D. turbinatus - 0.37 Mg C tree-1, followed by S. macrophylla - 0.23 Mg C tree-1 and T. grandis - 0.21 Mg C tree-1.